2010
DOI: 10.3844/ojbsci.2010.54.59
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Serum Cotinine Levels and Periodontal Status

Abstract: Problem statement:Smoking plays a significant role in the development of periodontal disease. Quantitative relation between smoking and increased severity of periodontal disease, by means of biochemical marker has not been described in Malaysian population. The present study was designed to apply serum cotinine measurement as a quantitative method to evaluate smoking levels in Malaysian patients and to correlate these levels with the severity of periodontal disease. Approach: The study group consisted of 80 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…The oral hygiene status, as represented by plaque scores, for smokers was 51.35 ± 11.27, and regression analyses demonstrated a significant relationship between plaque score, duration of smoking (years), and serum cotinine. This finding is in accordance with earlier studies [ 3 , 28 , 29 ]. However, other studies showed higher plaque levels in smokers [ 30 , 31 ], while some studies demonstrated less plaque levels in smokers [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The oral hygiene status, as represented by plaque scores, for smokers was 51.35 ± 11.27, and regression analyses demonstrated a significant relationship between plaque score, duration of smoking (years), and serum cotinine. This finding is in accordance with earlier studies [ 3 , 28 , 29 ]. However, other studies showed higher plaque levels in smokers [ 30 , 31 ], while some studies demonstrated less plaque levels in smokers [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 94%
“…This finding is in accordance with earlier studies [3, 28, 29]. However, other studies showed higher plaque levels in smokers [30, 31], while some studies demonstrated less plaque levels in smokers [32, 33].…”
Section: Discussionsupporting
confidence: 92%
“…14 Given its long half-life, serum cotinine levels have been successfully validated and used in scientific studies as a biomarker for tobacco exposure. 15 The present study included a convenient sample from the Belville South, a disadvantaged community located in the Western Cape Province in South Africa, characterized by a mixed ethnic background. Epidemiological data on tooth loss is essential to define treatment needs for public health policies.…”
Section: Tooth Loss In Relation To Serum Cotinine Levels -A Cross-sectional Study From the Belville South Area In South Africamentioning
confidence: 99%
“…18 Cotinine constitutes the principal metabolite of nicotine, and it has been used as a biomarker for tobacco exposure due to its long half-life. 15 The cut-off value of 15ng/ml was used in the current study to differentiate smokers from non-smokers, according to results from previously published literature. 14,19,20 Normality assumption of missing teeth variable was assessed through the Shapiro-Wilk test, which indicated that the data was skewed (p<0.001).…”
Section: Tooth Loss In Relation To Serum Cotinine Levels -A Cross-sectional Study From the Belville South Area In South Africamentioning
confidence: 99%
“…The bacteria found in dental plaque are commonly acknowledged as the primary cause of inflammatory periodontal diseases. 1,2 Traditionally, periodontal therapy aims to modify the periodontal environment to create conditions that facilitate the removal of dental plaque by patients.…”
Section: Introductionmentioning
confidence: 99%